2012
DOI: 10.1097/wnf.0b013e31826e6e6d
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Pharmacological Factors Associated With Impulse-Control Disorder Symptoms in Patients With Parkinson Disease

Abstract: Impulse-control disorder symptoms were more frequent in the patients with PD than in the poststroke patients with PD. Impulse-control disorder symptoms were related to younger age and exposure to monoaminooxidase-B inhibitors, and showed a nonlinear dose-response relationship with dopamine agonists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
80
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(86 citation statements)
references
References 20 publications
2
80
1
2
Order By: Relevance
“…Although ICDs are commonly under reported (Vilas, Pont-Sunyer, & Tolosa, 2011), it is estimated that between 10 and 14% of people with PD have ICDs (Giladi et al, 2007;Poletti et al, 2013;Weintraub, Potenza, Siderowf, & Voon, 2010), compared to between 1 and 8% within the general population (Dell'Osso, Altamura, Allen, Marazziti, & Hollander, 2006). Where explicit comparisons have been made between people with PD and matched controls, ICDs are around twice as common in Parkinson's patients than in controls (Rodriguez-Violante, Gonzalez-Latapi, Cervantes-Arriaga, Camacho-Ordonez, & Weintraub, 2015), although the difference can be even greater (Perez-Lloret, Rey, Fabre, Ory, Spampinato, Brefel-Courbon, Montastruc, & Rascol, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Although ICDs are commonly under reported (Vilas, Pont-Sunyer, & Tolosa, 2011), it is estimated that between 10 and 14% of people with PD have ICDs (Giladi et al, 2007;Poletti et al, 2013;Weintraub, Potenza, Siderowf, & Voon, 2010), compared to between 1 and 8% within the general population (Dell'Osso, Altamura, Allen, Marazziti, & Hollander, 2006). Where explicit comparisons have been made between people with PD and matched controls, ICDs are around twice as common in Parkinson's patients than in controls (Rodriguez-Violante, Gonzalez-Latapi, Cervantes-Arriaga, Camacho-Ordonez, & Weintraub, 2015), although the difference can be even greater (Perez-Lloret, Rey, Fabre, Ory, Spampinato, Brefel-Courbon, Montastruc, & Rascol, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, approximately 30% of patients with long-standing PD develop depression, which is partially attributable to the disease itself. Dementia in PD patients is related to the age of PD onset, rather than to the duration of the disease (6,9,14,16). Psychiatric symptoms -such as compulsive behavior, gambling etc.…”
Section: Introductionmentioning
confidence: 99%
“…A work by Pérez-Lloret and collaborators evaluated the incidence of impulse monitoring diseases and pharmacological variables associated with a group of sufferers with (n = 203) and without pd (n = 52, poststroke patients) in a sample of French patients (Pérez-Lloret et al, 2012). The disorders related to impulse control explored in the study were: gambling disorder, uncontrollable sexual behavior, compulsive shopping and uncontrollable eating.…”
Section: Overview Of the Experimental Work About The Relationship Betmentioning
confidence: 99%
“…For instance, treatment with dopaminergic drugs like Pramipexole -a partial/full D2/D3/D4 receptor agonist (Riba et al, 2008), Piribedil -a D2/D3 receptor agonist and D4 receptor antagonist (Micheli et al, 2015), Aripiprazole -a D2/D3/D4 receptor partial agonist (Gaboriau et al, 2014), and higher dosages of anti-Parkinsonian drugs (levodopa, dopamine equivalents or levodopa equivalents; Pontieri et al, 2015) have shown relatedness to gambling disorder in pd patients. On the other hand, dopamine related treatments like high dosages of anti-Parkinsonian drugs (levodopa, dopamine equivalents, levodopa equivalents; Pontieri et al, 2015), levodopa or dopamine agonists (Weintraub et al, 2010), type B monoamine oxidase inhibitors (Pérez-Lloret et al, 2012), increase the incidence of other impulse control disorders in pd patients based on different studies. On the other hand, deep brain stimulation (sub-thalamic nucleus) in advanced stage pd patients alters the judgment during "chasing losses" (Rogers et al, 2011).…”
Section: Conclusion Of the Experimental Work About The Association Bmentioning
confidence: 99%
See 1 more Smart Citation